Does the structure of working memory in EL children vary across age and two language systems?. Issue 2 (7th February 2019) - Swanson, H. Lee; Kudo, Milagros Fatima; Van Horn, M. Lee
ABSTRACT: This study examined the cross-sectional structure of working memory (WM) among elementary school English learners (ELs). A battery of WM tasks was administered in Spanish (L1) and English (L2) within five age groups (ages 6, 7, 8, 9, & 10). Confirmatory factor analysis showed a three-factor structure of WM emerged in both L1 and L2 administrations for each age group. The important findings, however, were: (1) the separation between the executive component and storage component (phonological loop) structure of WM increased as a function of age within both language systems, (2) the structure of WM supported a domain general phonological storage component and a domain general executive system across both language systems, and (3) the visual-spatial WM system shared minimal variance with the executive system. Taken together, the findings support Baddeley's multicomponent model (e.g., Baddeley & Logie, 1999. The multiple-component model. In A. Miyake & P. Shah (Eds.), Models of working memory: Mechanisms of active maintenance and executive control (pp. 28–61). Cambridge: Cambridge University Press) as a good fit to the structure of WM in EL children's English and Spanish language system.